Healthcare Spending, Institutional Quality and Economic Growth: A Panel Study of East Asian Countries - Nadeem Shahzad; Shabbir Ahmad; Hafiz Ghulam Mujaddad (International Journal of Emerging Multidisciplinaries: Social Science, 2026)
The study investigates the short- and long-run relationships among health spending, institutional quality, domestic investment, and foreign direct investment and their effects on the economic prosperity of East Asian countries from 2002 to 2020. Using data from 21 East Asian countries, we explore the relationship between healthcare expenditure and institutional frameworks and their impact on economic growth. Pooled ordinary least squares (OLS) and random-effects (RE) models are used. Relationships between the variables are estimated by using the Johansen-Fisher cointegration and Granger causality tests. The results reveal that health expenditure has a positive relationship with economic growth in the East Asian region in the RE model (0.2137, p